A Spotlight on Contemporary Language and Social Psychology Research: Selected Proceedings From the 16th International Conference on Language and Social Psychology. (September 2019) - Pitts, Margaret J.
This introduction to the special issue offers a brief report on the proceedings from the 16th International Conference on Language and Social Psychology (ICLASP16) and concludes with an invitation to participate in the upcoming ICLASP17 (Hong Kong, 2020). The nine papers selected for this special issue represent the diversity of scholarship and methodology presented at ICLASP16 (held in Edmonton, Canada, 2018). It includes student debut work, student-faculty collaborative pieces, keynote addresses, competitive papers, and an invited state-of-the-scholarship review.